2017
DOI: 10.1111/mec.14115
|View full text |Cite
|
Sign up to set email alerts
|

Pollinator identity and spatial isolation influence multiple paternity in an annual plant

Abstract: The occurrence and extent of multiple paternity is an important component of variation in plant mating dynamics. However, links between pollinator activity and multiple paternity are generally lacking, especially for plant species that attract functionally diverse floral visitors. In this study, we separated the influence of two functionally distinct floral visitors (hawkmoths and solitary bees) and characterized their impacts on multiple paternity in a self-incompatible, annual forb, Oenothera harringtonii (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
70
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(73 citation statements)
references
References 98 publications
2
70
1
Order By: Relevance
“…In comparison, solitary bees are much smaller, groom between floral visits, and when foraging pollen of O. harringtonii , do not necessary make contact with stigmas. Further, pollinator observations confirmed that visitation frequency and pollen dispersal distance did not differ between pollinator types, meaning that differences in paternity were likely due to pollinator behaviour and morphology (Rhodes et al., ). Using pollinator exclusion treatments and genetic analyses, the authors were able to isolate the effects of widely different pollinators, hawkmoths and bees, on multiple paternity.…”
mentioning
confidence: 81%
See 4 more Smart Citations
“…In comparison, solitary bees are much smaller, groom between floral visits, and when foraging pollen of O. harringtonii , do not necessary make contact with stigmas. Further, pollinator observations confirmed that visitation frequency and pollen dispersal distance did not differ between pollinator types, meaning that differences in paternity were likely due to pollinator behaviour and morphology (Rhodes et al., ). Using pollinator exclusion treatments and genetic analyses, the authors were able to isolate the effects of widely different pollinators, hawkmoths and bees, on multiple paternity.…”
mentioning
confidence: 81%
“…Interestingly, Rhodes et al. () did not find significant biparental inbreeding in open‐pollinated treatments, but seed families from both hawkmoth‐ and bee‐pollinated seed families did have some biparental inbreeding. Understanding why exclusive pollinator types increase biparental inbreeding compared to open‐pollinated plants requires further investigation.…”
mentioning
confidence: 93%
See 3 more Smart Citations